Ultrasonic machining of carbon fiber-reinforced plastic composites: a review - Asmael, Mohammed; Safaei, Babak; Zeeshan, Qasim; Zargar, Omid; Nuhu, Abubakar Abdussalam (Springer London Ltd, 2021)
Carbon fiber-reinforced plastic (CFRP) composites are extensively being applied in manufacturing sectors because of their extraordinary characteristics. However, CFRP composites often require some extra machining processes to improve the dimensional accuracy and component integrity of CFRP composites in manufacturing industries. The ultrasonic machining (USM) process progressively has been examined due to its greater ability in machining difficult to cut, brittle, and hard materials such as CFRP composites and due to its relatively low machining cost. Furthermore, USM shows to be a promising process with better surface quality, lower cutting force, less or no fiber fracture, laminate delamination, and lower tool wear rate. Recently, USM has been extensively investigated by many researchers for the machining of CFRP composites. This paper explores the literature and presents a comprehensive review of the advances in USM of CFRP composites by classifying the studies reported in two perspectives. First, the review summarizes most of the reported studies starting from 2011 to 2020 based on the applied USM process, equipment/system/platform used to carry out experiments, considered process parameters and output variables, and challenges investigated or gap filled. Then, the reported studies are summarized considering the type of USM process variant, CFRP composite, adopted process parameters on machining characteristics, and their respective results and conclusions. The aim is to present the current research status in USM of CFRP composites and thus provide guidance and foundation for future research.
Keywords: Carbon fiber– reinforced plastic composites; Ultrasonic machining; Process parameters; Machining characteristics